Privatizations Spark Socialist Backlash: Evidence from East Germany's Transformation - Anselm Hager; Moritz Hennicke; Werner Krause; Lukas Mergele (Center for Economic Studies and ifo Institute (CESifo), 2022)
The fall of the Berlin Wall in 1989 brought the end of socialism, yet pro-socialist sentiment regained momentum surprisingly quickly across Eastern Europe. Why did voters move back to an ideology that was associated with unfree elections and lackluster economic performance? This paper points to the rushed privatization of East European economies as one plausible driver of the revival of socialist voting. Using micro-level data from East Germany, we show that firm privatizations led to a marked resurgence of the former Socialist Unity Party. We argue that this effect is likely due to perceived inequity: Socialist voting thrived whenever firms were sold to Western elites, which East Germans took as a sign that capitalism was not meritocratic.
Keywords: 330; privatization; socialist backlash; structural change; democratization